Intermittent gaslift flows in vertical pipes - Hai, Duong Ngoc; Khang, Nguyen Thuc; Thien, Nguyen Duy (Vietnam Journal of Mechanics, 2007)
The paper presents the study results of intermittent gaslift. vertical flows using both experiment and theoretical models. To study the influence of medium thermophysical characteristics on the process efficiency, two gas-liquid systems are used in the experiments. The obtained results show that there is a critical gas injection volume, less than that the liquid slug cannot reach the top of the tubing. Correlations for prediction of liquid entrainment in gas core are also shown for two presented gas-liquid systems. Amodified dynamical model was developed. The model consists of a system of differential equations. The resulting system of equations is numerically solved. The numerical code is verified by using experimental data and calculation data of the other authors. Finally, the effects of system parameters are studied.